One Land Reform, Two Groups of Farmers in One Sugar Estate: A Case of Mkwasine - Francis Muromo (SciVision Publishers, 2023)
This study highlights how redistributive land reform in Mkwasine Sugar Estate created two groups of farmers in the same estate. The first group-the Chipiwa Settlement Scheme (CSS) was introduced in 1982 and the second group- the ‘A2 sugarcane farmers’ scheme, in the year 2005 and beyond. This creation has culminated into tensions and conflict between the two groups to this day. Using both primary and secondary data the study explores how the two groups of farmers were established in the estate. Study findings indicate that the CSS was more ordered than the A2 scheme which was introduced in response to the restlessness of war veterans and landless peasants over the slow pace of land reform in the first decade of independence. Findings furher indicate that the CSS farmers had sugarcane farming skills as well as experience as compared to some of the beneficiaries of the A2 scheme. The study recommends fair treatment by the government of both groups of farmers and that the former be allocated the same sizes of land or more than was given to the latter.